BixTey thermoelectric thin films sputtered at room temperature onto moving polymer web: effect of gas pressure on materials properties - Tao, X; Wan, K; Stuart, BW; Bilotti, E; Assender, HE (Elsevier, 2020)
Bismuth telluride was deposited onto a dynamic (25 m min−1) polyethylene terephthalate substrate at room temperature using direct current magnetron sputtering in preparation for roll-to-roll manufacture of flexible, low dimensional thermoelectric generators. This study explored the effect of sputtering pressure ranging from 0.03 to 0.6 Pa by adjusting argon flow rate from 50 to 500 sccm. Decreasing argon pressure from 0.6 to 0.03 Pa led to a more stoichiometric target-to-substrate atomic transfer. The coatings, deposited from a Te:Bi = 1.5 atomic ratio target, varied in composition ratio from 1.9 to 3.2, attributed to an obstructive phenomenon of sputtered Bi atoms during transport through the plasma region, under a higher working pressure. In addition, films grown under a lower pressure had wider and flatter grains (the aspect ratio of island width/height decreased from 40 (±1) at 50 sccm to 10 (±1) at 500 sccm for a ~80-nm coating), as indicated by images in atomic force microscopy. Electrical resistivity increased with pressure (0.9 ± 0.01 to 8.1 ± 0.2 mΩ•cm in a ~80-nm coating) due to a stronger carrier scattering mechanism and variations in the film composition and band gap. Seebeck coefficient increased with pressure (49.7 ± 0.9 to 84.0 ± 0.5 µV/K) attributable to an increased band gap and a possible energy barrier mechanism at grain boundaries leading to a carrier filtering effect. Power factor of the thermoelectric film was enhanced by decreasing pressure until the argon flow rate was below 250 sccm. The maximum power factor of the Bi-Te thin film achieved was 4.1 (±0.1) × 10−4 W/mK2 under 0.055 (±0.004) Pa of argon for a ~55 nm coating, which was achieved here by a real industrial-scale manufacturing process.